Advancing solar and heliospheric science through the ongoing development and support of atomic and laboratory plasma physics - Rivera, Y. J.; Landi, E.; Raymond, J. C.; Murphy, N. A.; Reep, J. W.; Barnes, W.; Higginson, A.; Young, P.; Daw, A.; Pesnell, W. D.; Paraschiv, A. R.; Lacatus, D. A.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
This paper outlines the necessity for the availability, accessibility, and expansion of atomic physics data and analysis tools for the meaningful interpretation of spectroscopic and polarimetric observations. As we move towards observing the Sun at higher spatio-temporal resolutions, and near-continuously at a range of wavelengths, it becomes critical to develop the appropriate atomic data and physics tools to facilitate scientific progress. We recommend the continued improvement and expansion of current databases to support the development of optically-thick/radiative transfer models, evaluate non-thermal and nonequilibrium ionization effects, and quantify uncertainties in atomic and molecular values. A critical long-term goal will require extending and strengthening collaborations across the atomic, solar/heliospheric, and laboratory plasma physics communities through the participation and training of early career scientists. We also recommend establishing funding for a centralized atomic physics resource made up of a comprehensive and user-oriented atomic database and modeling framework.